Modernity in Indian Novels: A Struggle for India’s Independence and Globalization - Regmi, Bhimnath (Myagdi Guru, 2024)
Indian literature, both inside and outside India, produced by various writers has an inner reflection of the Indus Valley Civilization and Vedic tradition, and also covers a wide range of contemporary thoughts. The majority of Indian literature produced in English, although there are collections of works that have been translated from Telugu, Tamil, Malayalam, Hindi, and other regional dialects, has a creative tradition. There is a movement among contemporary Indian writers to transform traditional India into modern India, which has inspired readers to make significant changes in their personal and professional lives. Every phase of an individual’s life is experimented with to deal with Indian civilization, ‘chutnification’ and weaving. This paper examines how India’s struggle for independence and the consequence of globalization added to modernity, and explores the interplay of tradition and innovation within Indian literary modernism. Prominent English writers who have migrated to the West have sliced modern human beings on the pages of literature, and made several attempts to connect their roots to the secular ideologies that are prevalent in India, and Indian ideas of a secular state can serve as a remedy for the current issues with people-centric politics.